Perancangan Kantor Pintar Berbasis Internet - Haziq Hazman; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Internet of things (IoT) is a concept that connecting any devices in daily life such as: machine, building, or other devices using internet network. One of the application is in the office area. Along with the development of technology, the automatic system in each area like an office is needed and demanded for the employee. Because accessing electronic devices in an office manualy causes lack of comfort and effectiveness in working, so the employee who works needs automatic control of all the electronic devices in the office. In this research, it was made a smart office plan based on the internet that connects to a smartphone as a controller that can control the devices in the office such as a lamp, a fan, and an electric socket. The components that are used namely: A mikrocontroller arduino as a brain in this system, an Espressif Smart Connectivity Platform(ESP) module as the Wi-Fi module, and an Android Smartphone as the controller and status checker of the smart office system. Keyword: Arduino, ESP, Android, Smart office, IoT.